A multi-site feasibility study to assess fever and wheezing in children after influenza vaccines using text messaging. Issue 50 (15th December 2017) - Stockwell, Melissa S.; Marchant, Colin D.; Wodi, A. Patrica; Barnett, Elizabeth D.; Broder, Karen R.; Jakob, Kathleen; Lewis, Paige; Kattan, Meyer; Rezendes, Anne Marie; Barrett, Angela; Sharma, Devindra; Fernandez, Nadira; et al.
Highlights: Text messaging is a scalable vaccine safety monitoring method. Non-medically attended event capture is valuable for pandemic influenza vaccination programs. We captured respiratory symptoms up to 42 days post influenza vaccination. Multi-site text message vaccine safety monitoring is feasible and acceptable. Abstract: Background: Using text messaging for vaccine safety monitoring, particularly for non-medically attended events, would be valuable for pandemic influenza and emergency vaccination program preparedness. We assessed the feasibility and acceptability of text messaging to evaluate fever and wheezing post-influenza vaccination in a prospective, observational, multi-site pediatric study. Methods: Children aged 2–11 years old, with an emphasis on children with asthma, were recruited during the 2014–2015 influenza season from three community-based clinics in New York City, and during the 2014–2015 and 2015–2016 seasons from a private practice in Fall River, Massachusetts. Parents of enrolled children receiving quadrivalent live attenuated (LAIV4) or inactivated influenza vaccine (IIV4) replied to text messages assessing respiratory symptoms (day 3 and 7, then weekly through day 42), and temperature on the night of vaccination and the next seven nights (day 0–7). Missing data were collected via diary (day 0–7 only) and phone. Phone confirmation was obtained for both presence and absence of respiratory symptoms. Reporting rates, fever (T ≥ 100.4 °F) frequency, proportion of wheezing and/or chest tightness reports captured via text message versus all sources (text, phone, diary, electronic health record) and parental satisfaction were assessed. Results: Across both seasons, 266 children were analyzed; 49.2% with asthma. Parental text message response rates were high (>70%) across sites. Overall, fever frequency was low (day 0–2: 4.1% [95% confidence interval (CI) 2.3–7.4%]; d3–7: 6.7% [95% CI 4.1–10.8%]). A third (39.2%) of parents reported a respiratory problem in their child, primarily cough. Most (88.2%) of the 52 wheezing and/or chest tightness reports were by text message. Most (88.1%) participants preferred text messaging over paper reporting. Conclusions: Text messaging can provide information about pediatric post-vaccination fever and wheezing and was viewed positively by parents. It could be a helpful tool for rapid vaccine safety monitoring during a pandemic or other emergency vaccination program. Trial registration: clinicaltrials.gov Identifier:NCT02295007 .